2018
DOI: 10.1093/ndt/gfy287
|View full text |Cite
|
Sign up to set email alerts
|

High-serum phosphate and parathyroid hormone distinctly regulate bone loss and vascular calcification in experimental chronic kidney disease

Abstract: In hyperphosphataemic CKD, a defective suppression of high PTH exacerbates HP-mediated osteogenic VSMC differentiation and reduces vascular levels of anti-calcifying sclerostin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…These data suggest that SP controlled duration is very important in PD patients. Large international studies have shown that elevated SP levels (hyperphosphatemia) are linked with a number of serious clinical complications, including vascular calcification [11,12] and left ventricular hypertrophy [13], as well as increased all-cause mortality and PD withdrawal in patients undergoing dialysis [5][6][7][8][9][10][14][15][16][17]. In the Dialysis Outcomes and Practice Patterns Study (DOPPS), SP levels decreased over time in all countries, and higher SP levels were associated with greater all-cause mortality risk in both baseline and time-dependent models [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that SP controlled duration is very important in PD patients. Large international studies have shown that elevated SP levels (hyperphosphatemia) are linked with a number of serious clinical complications, including vascular calcification [11,12] and left ventricular hypertrophy [13], as well as increased all-cause mortality and PD withdrawal in patients undergoing dialysis [5][6][7][8][9][10][14][15][16][17]. In the Dialysis Outcomes and Practice Patterns Study (DOPPS), SP levels decreased over time in all countries, and higher SP levels were associated with greater all-cause mortality risk in both baseline and time-dependent models [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline data were collected on demographic characteristics (age, gender, and BMI), reasons for ESRD, medical histories (hypertension, diabetic mellitus, and hepatitis B virus infection), PD vintage, PD modality, and peritoneal equilibration test (PET) types (1 month after PD). Data over time of systolic blood pressure; diastolic blood pressure; left ventricular ejection fraction; dialysate glucose concentration; 24-h PD ultrafiltrate volume; 24-h urine volume; weekly total KT/V; serum levels of Cr, albumin, and calcium; intact parathyroid hormone; and blood hemoglobin were collected at baseline (before PD, 0 month) and at 6,12,24,36,48,72,96, and 120 months after PD. In order to evaluate the detailed information of SP, levels at 0 month and at 3,6,9,12,18,24,30,36,48,72,96, and 120 months after PD were collected and recorded.…”
Section: Data Collection and Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the common view that traditional risk factors may be inferior as compared to novel biomarkers predicting cardiovascular outcomes in CKD [27,28], our results indicate that conventional risk factors, that is age, sex, diabetes, BMI and cholesterol, outperformed many novel biomarkers, suggesting that traditional risk factors are of paramount importance for VC in uraemia. Five biomarkers selected by the RLS algorithm were bone metabolism-related markers, that is, sRANKL, fT3, CTX, OPG and iPTH, suggesting the close interplay between disturbed bone metabolism and ectopic VC [29,30]. In addition, RLS yielded several novel VC biomarkers for which clinical and potential pathophysiological implications are noted in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that high PTH is a main contributor to the progression of vascular calcification in hemodialysis patients . However, the study of the role of FGF23 in this regard has yielded contradictory results .…”
Section: Bone Mineral Disease and Mortalitymentioning
confidence: 99%